Technology adoption and access to credit via mobile phones - Apoorv Gupta; Jacopo Ponticelli; Andrea Tesei (Queen Mary University of London, School of Economics and Finance, 2019)
Farmers in developing countries often lack access to timely and reliable information about modern technologies that are essential to improve agricultural productivity. The recent diffusion of mobile phones has the potential to overcome these barriers by making information available to those previously unconnected. In this paper we study the effect of mobile phone network expansion in rural India on adoption of high yielding variety seeds and chemical fertilizers. Our empirical strategy exploits geographical variation in the construction of mobile phone towers under a large government program targeting areas without existing coverage. To explore the role of mobile phones in mitigating information frictions we analyze the content of 1.4 million phone calls made by farmers to a major call center for agricultural advice. Farmers seek advice on which seed varieties and fertilizers better meet their needs and how to use them. We find that areas receiving mobile phone coverage experience higher adoption of these technologies. We also observe that farmers are often unaware of the eligibility criteria and loan terms offered by subsidized credit programs. Consistently, we find that areas receiving mobile phone coverage experience higher take-up of agricultural credit.
Keywords: G21; Q16; E51; 330; India; Agriculture; HYV Seeds; Credit Card